FORMATION OF PATRIOTISM IN THE FRAMEWORK OF THE PROGRAM " RUHANI ZHANGYRU " AS A HISTORICAL FACTOR OF THE DEVELOPMENT OF KAZAKHSTAN - Tuyakoval, A.E. (Academic Journal of Physical and Chemical Sciences, 2018)
In this article, the author examines Kazakhstan's patriotism, which is a new paradigm of state policy and ideology. Undoubtedly, its appearance and approval in the Republic of Kazakhstan was associated with the strengthening of the state's independence. Today, in the age of a rapidly changing picture of the world and new global challenges to mankind, the need to educate the true patriots of our country is growing: "We need to educate ourselves and our children with new Kazakhstan patriotism. This, above all, is the pride of the country and its achievements. " Very topical, this year the Kazakh language was given the status of the state language in Kazakhstan. The issue of preserving the symbol of our statehood - Kazakh language became one of the key from the first day of independence